The Role Of Social Media In Shaping Students' Consumer Behavior - Al kautsar; Zulkiram; Ade Bustanus (Yayasan Yusda Edu Indonesia, 2026)
The development of social media has changed many aspects of students' lives, including how they obtain information, communicate, and make decisions about shopping. The constant emergence of digital content has led students to increasingly follow various trends, product advertisements, and lifestyles emerging online. This study aims to examine how social media influences students' shopping habits and identify factors that make them more likely to overspend. This study used a literature review method with a descriptive qualitative approach. The data were obtained from studying various relevant scientific sources, such as books, articles from domestic and international journals, and previous research accessed through Google Scholar, SINTA, DOAJ, and Garuda. The analysis was conducted by identifying, categorizing, understanding, and combining various findings regarding social media use and students' shopping attitudes. This study shows that social media plays a significant role in shaping excessive shopping habits. This occurs due to several factors, such as the frequency of digital platform use, the influence of famous users or content creators, popular trends, and the fear of missed opportunities (FOMO) effect. This situation leads students to purchase items, typically driven by personal desires, a desired self-image, and a desire for social acceptance. This study found that social media plays a significant role in changing the way students purchase items and influencing their views on current needs and lifestyles.